Tradução e estudo da Victorini ars, de Máximo Vitorino - Alves, Ana Flávia Franco Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Este trabalho apresenta a primeira tradução vernácula do texto de Máximo Vitorino, encontrado no Volume VI da obra Grammatici Latini de Heinrich Keil, bem como uma análise introdutória de seu conteúdo sobre a métrica clássica latina. A pesquisa examina como Máximo Vitorino, em sua ars grammatica (arte gramatical), aborda a estrutura fonológica e métrica do latim de maneira didática, articulando definição, fonética, categorias gramaticais e elementos métricos em um formato de perguntas e respostas que lhe confere uma organização singular. A tradução e estudo buscam elucidar as dificuldades linguísticas e culturais presentes na obra, utilizando comparações com outros manuais técnicos da época, como os de Donato (1857), Palêmon e Sérgio Honorato. Para enriquecer a compreensão dos preceitos gramaticais e métricos descritos por Vitorino. A tradução foi realizada com base em instrumentos filológicos e acompanhada de comentários que visam esclarecer dificuldades linguísticas, terminológicas e métricas encontradas no texto latino. O estudo, dividido em fases de tradução e análise, propõe uma reflexão sobre aspectos prosódicos do latim, frequentemente inacessíveis às línguas modernas, além de situar a contribuição de Máximo Vitorino dentro da tradição dos gramáticos latinos.

This work presents the first vernacular translation of the text of Maximus Victorinus, found in Volume VI of Heinrich Keil’s Grammatici Latini, as well as an introductory analysis of its content on classical Latin metrics. The research examines how Maximus Victorinus, in his ars grammatica (grammatical art), approaches the phonological and metrical structure of Latin in a didactic manner, articulating definition, phonetics, grammatical categories, and metrical elements in a question-and-answer format that grants the treatise a distinctive organization. The translation and study aim to elucidate the linguistic and cultural difficulties present in the work, drawing comparisons with other technical manuals of the period, such as those by Donatus (1857), Palaemon, and Sergius Honoratus. To enrich the understanding of the grammatical and metrical precepts described by Victorinus, the translation was carried out using philological tools and accompanied by commentary intended to clarify linguistic, terminological, and metrical challenges found in the Latin text. Divided into phases of translation and analysis, the study proposes a reflection on prosodic aspects of Latin, often inaccessible to modern languages, as well as situating the contribution of Maximus Victorinus within the tradition of the Latin grammarians.
Translation and study of Victorini ars, from Maximus Vixtorinus
Keywords: Máximo Vitorino; Tradução; Métrica clássica; Gramática latina; Artes grammaticae; Translation; Classic metric; Latin grammar